Frequency of ABO Blood Group Discrepancies and its Classification into Groups in Tertiary Care Hospital Karachi - Sumera Shaikh; Saba Jamal; Fatima Mairaj; Areebah Asim (ziauddin University, 2019)
Background: The aim of this study was to document the frequency of ABO discrepancies through ABO blood group test performed by the tube technique method. It was conducted on residents of Karachi in Ziauddin hospital, which were then categorized into four groups. Methods: Descriptive, cross-sectional type of study was conducted at the Blood Bank of Dr. Ziauddin Hospital, North Nazimabad and Clifton campuses in Karachi Pakistan. A total of 1522 samples were included with the exclusion criteria of neonates and infants of up to the age of 6 months. The time frame was from September 2016 to March 2017. Blood samples were collected from a superficial vein by trained phlebotomists and submitted to the blood bank department in 2 tubes, purple top vacutainer tube containing Di-potassium Ethylene Diamine Tetra Acetic Acid (K2 EDTA) anticoagulant and red top vacutainer tube containing clotted blood. Blood group testing was done by tube technique by a researcher and then redone by the senior technologist of blood bank to control bias. Results: 1557 hospitalized patients (854 males and 703 females) from various clinical specialties in Ziauddin Hospital, Karachi and other hospitals were included for ABO blood grouping. The male to female ratio was 1.2:1 with the age range from 9 months to 92 years. ABO discrepancies were positive in 18 out of 1557 Patients (1.1%). Male to female ratio among positive ABO discrepancies were 1:5 (11 males and 7 females out of 18 patients). Four groups of ABO discrepancies were formed. The most common one being group I discrepancies which had 12 out of 18 Patients (66.7%). Group II discrepancies had 2 out of 18 Patients (11.1%). Group III discrepancies had 1 out of 18 Patients (5.5%) and Group IV discrepancies consisted of 3 out of 18 Patients (16.7%). Conclusion: Forward and reverse groupings are essential to blood group testing for assigning the correct ABO blood group to the individual. Those ABO discrepancies in which forward and reverse grouping are not matched to each other can cause severe transfusion reactions resulting fatal for life. Therefore, it is necessary to ensure that the correct ABO blood product is transfused to save a life. Thus, reverse grouping should be strictly adopted in every blood bank and transfusion services as a routine practice.